Teaching Children and Parents to Understand Dog Signaling - Meints, Kerstin; Brelsford, Victoria; De Keuster, Tiny (Frontiers in Veterinary Science, 2018)
Safe human-dog relationships require understanding of dogs’ signalling.. As children are at particularly high risk of dog bites, we investigated how children from 3 to 5 years and parents perceive and interpret dogs’ distress signalling gestures. All participants were then taught how to link their perception of the dog with the correct interpretation of the dogs’ behavioural signals and tested again. Results show a significant increase in learning for children and adults, with all showing greater understanding of dogs’ signalling after intervention. Better learning effects were found with increasing age and depended on the type of distress signalling of the dogs. Effects endured over time and it can be concluded that children and adults can be taught to interpret dogs’ distress signalling more correctly. Awareness and recognition of dog’s stress signalling can be seen as an important first step in understanding the dog’s perspective and are vital to enable safe interactions.